2013
DOI: 10.4253/wjge.v5.i11.574
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a quality indicator format for endoscopic ultrasound

Abstract: AIM:To perform a quality control (QC) review of endoscopic ultrasound (EUS) with emphasis on current consensus established quality indicators. METHODS:A national quality control study of EUS was performed with expanded international comparison. Ten different healthcare institutions in Israel participated in coordination with University of Chicago Medical Center. Each Israeli center provided ten patient reports, compared with twenty reports from University of Chicago Medical Center. Quality indicator forms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Likewise, Coe et al found endoscopist adherence to EUS QIs over an eight-year span to be strictly related to significant improvement in all EUS aspects (15). Lachter et al explored adherence to EUS QIs at ten different Israeli medical centers keeping as standard the University of Chicago and observed that an overall improvement in documented quality of EUS exams was found in centers ensuring comprehensive documentation and stronger guideline adherence (16). Further confirm of these findings was provided in the study by Schwab et al, where significant improvements were demonstrated in QI adherence and thus EUS reporting and delivery quality in 2013-2014 reports as compared to 2009 results (17).…”
Section: Importance Of Quality Assessment In Eus Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Coe et al found endoscopist adherence to EUS QIs over an eight-year span to be strictly related to significant improvement in all EUS aspects (15). Lachter et al explored adherence to EUS QIs at ten different Israeli medical centers keeping as standard the University of Chicago and observed that an overall improvement in documented quality of EUS exams was found in centers ensuring comprehensive documentation and stronger guideline adherence (16). Further confirm of these findings was provided in the study by Schwab et al, where significant improvements were demonstrated in QI adherence and thus EUS reporting and delivery quality in 2013-2014 reports as compared to 2009 results (17).…”
Section: Importance Of Quality Assessment In Eus Practicementioning
confidence: 99%
“…Therefore, authors concluded that QI implementation facilitates effective high-quality EUS exams by ensuring comprehensive documentation while limiting error (17). However, adherence to quality guidelines remains still jeopardized across several centers, with some items such as description of FNA, or listing of adverse events largely lacking from procedural documentation (16).…”
Section: Importance Of Quality Assessment In Eus Practicementioning
confidence: 99%
“…[ 18 ] In one survey at a Chicago EUS for experts seminar, 75% of echoendoscopists reported using the stylet when putting in the needle and 25% have taken to removing it. [ 19 ] No study which clearly examined the head-to-head benefits to risks of rounded/ball-tip stylets to beveled stylets for EUS-FNA has appeared.…”
Section: Fnamentioning
confidence: 99%
“…Unlike digestive endoscopy, the quality of reporting in endoscopic ultrasound (EUS) has not been thoroughly evaluated and a reference standard is lacking 13 14 15 16 17 . EUS is a complex technique with several diagnostic and therapeutic applications 18 19 20 21 22 23 24 .…”
Section: Introductionmentioning
confidence: 99%